2014
DOI: 10.1513/annalsats.201406-232oc
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Changes after Lung Transplantation

Abstract: Rationale: Neurocognitive impairments are associated with reduced quality of life and may adversely affect medical compliance, but their prevalence after lung transplantation has not been extensively studied.Objectives: To examine the frequency of neurocognitive impairment after lung transplantation and to examine perioperative factors affecting post-transplant neurocognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 40 publications
(36 reference statements)
2
43
0
Order By: Relevance
“…Our LT-VLA data and recent investigations focused on other individual health domains important in lung transplantation ( e.g ., depression and anxiety(9, 10, 14, 19, 21), physical functioning/disability(12, 17, 28), symptom burden(16, 18), and cognitive impairment(13, 15, 22)) suggest that increased attention to individual health domains may ultimately yield more informative data that can be used to design interventions to improve HRQL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our LT-VLA data and recent investigations focused on other individual health domains important in lung transplantation ( e.g ., depression and anxiety(9, 10, 14, 19, 21), physical functioning/disability(12, 17, 28), symptom burden(16, 18), and cognitive impairment(13, 15, 22)) suggest that increased attention to individual health domains may ultimately yield more informative data that can be used to design interventions to improve HRQL.…”
Section: Discussionmentioning
confidence: 99%
“…(922) Nonetheless, relatively few studies focused on HRQL itself as a primary outcome in lung transplantation have been published since the LAS overhaul. (23) Thus, given the clinical primacy of HRQL, there is a need for contemporary information on the effect of lung transplantation on general and respiratory-specific HRQL…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lower cerebral perfusion pressure was found to be associated with doubling the risk of delirium in the same patient sample, as well as increasing the duration and severity of delirium 12 . Finally, delirium during the index hospitalization in lung transplant recipients without cystic fibrosis has been associated with worse post-transplant neurocognitive function 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is common following lung transplant and has been shown to be associated with poorer clinical outcomes (8) and future cognitive impairment (9). Several recent studies have suggested that poorer intraoperative hemodynamic function may be associated with adverse neurocognitive outcomes among patients undergoing surgical procedures requiring single-lung ventilation (10,11).…”
mentioning
confidence: 99%